Toughened hard alloy for improving WC grain morphology and preparation method thereof

By adding molybdenum carbide and cobalt to WC-Co carbide and using ball milling process and inhibitor elements, the WC grain morphology is adjusted to make it spherical, which solves the insufficient fatigue resistance and impact toughness of cemented carbide The problem of this problem has achieved higher flexural strength and alloy density, significantly improving the overall performance of cemented carbide.

CN119287238APending Publication Date: 2025-01-10ZIGONG CEMENTED CARBIDE CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411234088.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The prior art has challenges in improving the fatigue resistance and impact toughness of WC-Co-based cemented carbides, especially when maintaining the hardness and strength of materials, it is difficult to effectively improve the flexural strength and toughness, and a variety of metal oxides are also used. Adding can lead to ingredient control difficulties and increased costs.

Method used

By adding a specific amount of molybdenum carbide (Mo2C or MoC) and cobalt to WC-Co carbide, combining ball milling process and inhibitor elements, the WC grain morphology is adjusted to make it appear spherical, Cr and Mo element solid When dissolved into the bonded phase, Mo2C is preferentially dissolved into the Co phase, affecting the dissolution and growth mechanism of WC, resulting in the WC grains becoming smaller and passivated, thereby improving the toughness and fatigue resistance of the alloy.

Benefits of technology

The WC grain morphology has been improved, the fatigue impact resistance and toughness of the alloy are improved, while maintaining high flexural strength and density, significantly improving the overall performance of the cemented carbide.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287238A_ABST
    Figure CN119287238A_ABST
Patent Text Reader

Abstract

The invention discloses a toughened hard alloy for improving WC grain morphology, which belongs to the technical field of hard alloy materials and comprises 0.5-5% of molybdenum carbide, 10-15% of cobalt, 0.5-3% of chromium carbide and the balance of WC. According to the preparation method, the specific ball milling technology and the combined action of inhibitor elements are adopted, so that WC grains are in a spheroidal shape, Cr and Mo elements are subjected to solid solution in a binding phase to strengthen the binding phase, Mo2C is prior to WC to be dissolved in a Co phase, so that the normal dissolution, precipitation and growth mechanism of WC is influenced, and the phenomenon of passivation occurs while the WC grains become smaller is caused. And the binding phase is uniformly distributed, the densification degree of the alloy is high, and excellent fatigue impact resistance is embodied while the obdurability is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cemented carbide materials, in particular to a toughened cemented carbide with improved WC grain morphology and a preparation method thereof. Background Art

[0002] WC-Co based cemented carbide has the characteristics of high strength, high hardness and corrosion resistance, and is widely used in various manufacturing, mining, excavation and other work scenarios. However, cemented carbide is a brittle material. It will deform when impacted during use and is prone to brittle fracture. When the Co content is 10-15wt%, with the increase of WC grain size, although the fracture toughness of the alloy can increase, the bending strength decreases and the impact toughness value also decreases. In cemented carbide tools, if you want to increase the service life of the material, you need to improve the fatigue resistance as much as possible while meeting the hardness and strength required for use. The usual options are: ①. Strengthen the bonding phase; ②. Strengthen the hard phase; ③ Improve the WC grain morphology, etc.

[0003] In the currently disclosed patents, for improving the toughness of cemented carbide, different hard phase-binder phase ratios are selected to improve the toughness of cemented carbide; or while keeping the ratio of hard phase to binder phase unchanged, the following are made: ① adding metal oxides, carbides, rare earth elements, etc. to produce solid solution strengthening, precipitation strengthening and other strengthening effects on the binder phase and hard phase of the alloy, so that crack propagation is hindered; ② selecting WC mixed crystal structure, so that the cemented carbide has both the characteristics of fine grain size WC high hardness and the characteristics of coarse grain size and good toughness. CN109957697A patent discloses a method for adding metal oxides to improve the toughness of cemented carbide, characterized in that the batching step adds ZrO2 and La2O3 to WC-8Co cemented carbide, and the amounts thereof are 0.1-0.5wt% and 0.1-0.5wt% of the weight of the mixture, respectively. The mechanism is to use La2O3 to inhibit the growth of alloy grains, and to use ZrO2 to solid-dissolve in the binder phase to inhibit the expansion of cracks in the binder phase, thereby improving the toughness of the alloy. This method can strengthen the bonding phase and significantly improve the toughness of cemented carbide, but the addition of multiple metal oxides makes it difficult to control the alloy phase composition, and the carbon content is not easy to control. Patent CN111088450A discloses a rare earth added ultrafine grain high toughness WC-10Co cemented carbide material, characterized in that it contains the following components by weight percentage: 88.7%-89.1% tungsten carbide, 10% cobalt, 0.5% vanadium carbide, 0.3% chromium carbide, 0.1%-0.5% praseodymium oxide or 0.1%-0.5% neodymium oxide; praseodymium oxide and neodymium oxide as inhibitors can inhibit the growth of WC grains and improve the hardness of cemented carbide, while also improving the toughness of cemented carbide. However, rare earth elements themselves as inhibitors are prone to cause component segregation, resulting in defects such as pores, and are accompanied by problems such as increased costs and complex processes.

[0004] Therefore, providing a simple process and low cost to improve the WC grain morphology toughened cemented carbide and a preparation method thereof is a technical problem that technical personnel in the field need to solve urgently. Summary of the invention

[0005] In view of this, the present invention provides a toughened cemented carbide with improved WC grain morphology and a preparation method thereof, while ensuring the static performance of the original grade of cemented carbide.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] A toughened cemented carbide with improved WC grain morphology, comprising the following raw materials in percentage by mass:

[0008] Molybdenum carbide 0.5-5%, cobalt 10-15%, chromium carbide 0.5-3%, and the balance is WC.

[0009] The carbon content of the total mass of W and C in the above raw materials ranges from 6.08wt% to 6.20wt%.

[0010] Further, the molybdenum carbide is Mo2C and / or MoC

[0011] The present invention also provides a method for preparing the above-mentioned WC grain morphology-improved toughened cemented carbide, comprising the following steps:

[0012] (1) Weigh the raw materials according to the above mass percentages;

[0013] (2) mixing the weighed raw materials and wet-grinding them to obtain a uniform and fine mixture, drying the mixture, sieving the obtained powder, and then pressing it into a compact;

[0014] (3) The obtained compact is placed in a vacuum low-pressure sintering furnace for dewaxing and sintering to obtain a toughened cemented carbide with improved WC grain morphology.

[0015] Furthermore, in step (2), the wet grinding medium is hexane, the ball milling speed is 60-80 r / min, the grinding body is a Φ6.35 mm alloy rod, the ball-to-material ratio is 3:1-5:1, and the ball milling time is 18-32 h.

[0016] The drying in step (2) is vacuum drying, the drying temperature is 70-80° C., and the drying time is 15-30 min.

[0017] Furthermore, the sieving particle size in step (2) is 40-60 mesh.

[0018] Furthermore, the pressing method in step (2) is to press the green compact at a pressure of 8-10 MPa for 5-10 seconds.

[0019] Furthermore, the dewaxing sintering method in step (3) is: keeping warm at 380-420°C for 0.5h, then heating to 1400-1470°C under vacuum, filling with argon to 1MPa-5MPa and sintering for 1-4h.

[0020] The beneficial effects of the present invention are as follows: the present invention adopts a specific ball milling process and the combined effect of inhibitor elements to make the WC grains present a spherical morphology, Cr and Mo elements are dissolved in the bonding phase to strengthen the bonding phase, and Mo2C is dissolved in the Co phase before WC, thereby affecting the normal dissolution, precipitation and growth mechanism of WC, resulting in the phenomenon of passivation while the WC grains become smaller. The bonding phase is evenly distributed, the alloy has a high degree of densification, and excellent fatigue impact resistance is reflected while ensuring strength and toughness. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a metallographic photograph of WC-Co cemented carbide with Mo and Cr inhibitors added in Example 1 of the present invention;

[0022] Figure 2 This is a metallographic photograph of WC-Co cemented carbide without adding Mo2C in comparative example 1 of the present invention. DETAILED DESCRIPTION

[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1

[0025] A toughened cemented carbide with improved WC grain morphology

[0026] (1) Weigh the following by mass percentage: 1.5% molybdenum carbide powder (Mo2C), 12% cobalt powder, 0.5% chromium carbide powder, and 86% WC with a grain size of 4.0 μm; the total carbon content of the mixture is adjusted to 6.14%.

[0027] (2) The weighed raw materials were mixed and placed in a grinding container, and then hexane was added, and a Φ6.35 mm alloy rod was placed as a grinding body, the ball-to-material ratio was controlled to be 3.5:1, the ball mill speed was adjusted to 70 r / min, and wet grinding was performed for 1200 min; the mixed material was vacuum dried at 75° C. to completely remove the hexane, passed through a 40-mesh sieve, and then pressed into a green compact at a pressure of 8 MPa for 10 s;

[0028] (3) The obtained compact is placed in a 3 MPa vacuum low-pressure sintering furnace and first heated to 400°C and kept warm for 30 minutes; then the compact is placed in a vacuum environment, argon is introduced until the ambient pressure reaches 3 MPa, and the temperature is continued to rise to 1450°C, sintered for 2.5 hours, and the compact is taken out as it cools in the furnace to obtain a toughened cemented carbide with improved WC grain morphology.

[0029] The fracture surface of the fired sample was prepared and corroded by immersion in a dilute FeCl3 solution (HCl mass concentration 5%) for 10 minutes. The sample was then taken out, rinsed with anhydrous ethanol, dried, and the fracture surface was observed under an electron microscope. The WC passivation rate was measured by mathematical statistics method and was found to be 73%.

[0030] Example 2

[0031] (1) Weigh the following by mass percentage: 1.0% molybdenum carbide powder (Mo2C), 13% cobalt powder, 0.6% chromium carbide powder, and 85.4% WC with a grain size of 3.5 μm; the total carbon content of the mixture is adjusted to 6.14%.

[0032] (2) The weighed raw materials were mixed and placed in a grinding container, and then hexane was added, and a Φ6.35 mm alloy rod was placed as a grinding body, the ball-to-material ratio was controlled to be 3:1, the ball mill speed was adjusted to 70 r / min, and wet grinding was performed for 1400 min; the mixed material was vacuum dried at 70° C. to completely remove the hexane, passed through a 40-mesh sieve, and then pressed into a compact at a pressure of 8 MPa for 8 seconds;

[0033] (3) The obtained compact is placed in a 3 MPa vacuum low-pressure sintering furnace and first heated to 400°C and kept warm for 30 minutes; then the compact is placed in a vacuum environment, argon is introduced until the ambient pressure reaches 3 MPa, and the temperature is continued to rise to 1450°C, sintered for 2.5 hours, and the compact is taken out as it cools in the furnace to obtain a toughened cemented carbide with improved WC grain morphology.

[0034] The fracture surface of the fired sample was prepared and corroded by immersion in a dilute FeCl3 solution (HCl mass concentration 5%) for 10 minutes. The sample was then taken out, rinsed with anhydrous ethanol, dried, and the fracture surface was observed under an electron microscope. The WC passivation rate was measured by mathematical statistics and was found to be 65%.

[0035] Example 3

[0036] (1) Weigh the following by mass percentage: 1.0% molybdenum carbide powder (Mo2C), 15% cobalt powder, 1.0% chromium carbide powder, and 83% WC with a grain size of 4.0 μm; the total carbon content of the mixture is adjusted to 6.10%.

[0037] (2) The weighed raw materials were mixed and placed in a grinding container, and then hexane was added, and a Φ6.35 mm alloy rod was placed as a grinding body, the ball-to-material ratio was controlled to be 3:1, the ball mill speed was adjusted to 70 r / min, and wet milling was performed for 1400 min; the mixed material was vacuum dried at 70° C. to completely remove the hexane, passed through a 40-mesh sieve, and then pressed into a green compact at a pressure of 8 MPa for 10 s;

[0038] (3) The obtained compact is placed in a 3 MPa vacuum low-pressure sintering furnace and first heated to 400°C and kept warm for 30 minutes; then the compact is placed in a vacuum environment, argon is introduced until the ambient pressure reaches 3 MPa, and the temperature is continued to rise to 1450°C, sintered for 2.5 hours, and the compact is taken out as it cools in the furnace to obtain a toughened cemented carbide with improved WC grain morphology.

[0039] The fracture surface of the fired sample was prepared and corroded by immersion in a dilute FeCl3 solution (HCl mass concentration 5%) for 10 minutes. The sample was then taken out, rinsed with anhydrous ethanol, dried, and the fracture surface was observed under an electron microscope. The WC passivation rate was measured by mathematical statistics and was found to be 85%.

[0040] Example 4

[0041] (1) Weigh the following by mass percentage: 0.6% molybdenum carbide powder (MoC), 15% cobalt powder, 1.0% chromium carbide powder, and 83.4% WC with a grain size of 4.0 μm; the total carbon content of the mixture is adjusted to 6.11%.

[0042] (2) The weighed raw materials were mixed and placed in a grinding container, and then hexane was added, and a Φ6.35 mm alloy rod was placed as a grinding body, the ball-to-material ratio was controlled to be 4:1, the ball mill speed was adjusted to 70 r / min, and wet grinding was performed for 1400 min; the mixed material was vacuum dried at 70° C. to completely remove the hexane, passed through a 40-mesh sieve, and then pressed into a compact at a pressure of 8 MPa for 8 seconds;

[0043] (3) The obtained compact is placed in a 3 MPa vacuum low-pressure sintering furnace and first heated to 400°C and kept warm for 30 minutes; then the compact is placed in a vacuum environment, argon is introduced until the ambient pressure reaches 3 MPa, and the temperature is continued to rise to 1450°C, sintered for 2.5 hours, and the compact is taken out as it cools in the furnace to obtain a toughened cemented carbide with improved WC grain morphology.

[0044] The fracture surface of the fired sample was prepared and corroded by immersion in a dilute FeCl3 solution (HCl mass concentration 5%) for 10 minutes. The sample was then taken out, rinsed with anhydrous ethanol, dried, and the fracture surface was observed under an electron microscope. The WC passivation rate was measured by mathematical statistics and was found to be 82%.

[0045] Comparative Example 1

[0046] A hard alloy

[0047] (1) Weigh by mass percentage: 12% cobalt powder, 0.5% chromium carbide powder, and 87.5% WC with a grain size of 4.0 μm;

[0048] (2) The weighed raw materials were mixed and placed in a grinding container, and then hexane was added, and a Φ6.35 mm alloy rod was placed as a grinding body, the ball-to-material ratio was controlled to be 2.5:1, the ball mill speed was adjusted to 70 r / min, and wet milling was performed for 1400 min; the mixed material was dried to completely remove the hexane, passed through a 40-mesh sieve, and then pressed into a compact at a pressure of 8 MPa for 10 s.

[0049] (3) The obtained compact is placed in a 3MPa vacuum low-pressure sintering furnace and heated to 400°C for 30 minutes; then the compact is placed in a vacuum environment, argon is introduced until the ambient pressure is 3MPa, and the temperature is continued to rise to 1450°C, sintered for 2.5 hours, and the compact is taken out of the furnace while cooling to obtain a cemented carbide.

[0050] The fracture surface of the fired sample was prepared and corroded by immersion in a dilute FeCl3 solution (HCl concentration 5%) for 10 minutes. The sample was then taken out, rinsed with anhydrous ethanol, dried, and the fracture surface was observed under an electron microscope. The WC passivation rate was measured by mathematical statistics and was found to be 42%.

[0051] Comparative Example 2

[0052] (1) Weigh the following by mass percentage: 0.2% molybdenum carbide powder (Mo2C), 15% cobalt powder, 0.5% chromium carbide powder, 0.1% cerium oxide, and 84.2% WC with a grain size of 4.0 μm;

[0053] (2) The weighed raw materials were mixed and placed in a grinding container, and then hexane was added, and a Φ6.35 mm alloy rod was placed as a grinding body, the ball-to-material ratio was controlled to be 3:1, the ball mill speed was adjusted to 70 r / min, and wet grinding was performed for 1200 min; the mixed material was vacuum dried at 70° C. to completely remove the hexane, passed through a 40-mesh sieve, and then pressed into a compact at a pressure of 8 MPa for 8 seconds;

[0054] (3) The obtained compact is placed in a 3 MPa vacuum low-pressure sintering furnace and first heated to 400°C and kept warm for 30 minutes; then the compact is placed in a vacuum environment, argon is introduced until the ambient pressure reaches 3 MPa, and the temperature is continued to rise to 1450°C, sintered for 2.5 hours, and the compact is taken out as it cools in the furnace to obtain a toughened cemented carbide with improved WC grain morphology.

[0055] The fracture surface of the fired sample was made and corroded by immersion in a dilute FeCl3 solution (HCl mass concentration 5%) for 10 minutes. The sample was then taken out, rinsed with anhydrous ethanol, dried, and the fracture surface was observed under an electron microscope. The WC passivation rate was measured by mathematical statistics and was found to be 45%.

[0056] Test example

[0057] (1) Metallographic structure

[0058] like Figure 1 is the metallographic diagram of the cemented carbide in Example 1, Figure 2 This is the metallographic image of the cemented carbide in Example 1. It can be found that when Mo2C is not added, the WC grains in the alloy are Figure 2 The sharp morphology shown in the figure shows that there are abnormally grown grains. When Mo2C is added, the WC grains in the alloy show Figure 1 The "passivated" morphology shown has good grain uniformity.

[0059] (2) Material properties

[0060] The alloy products prepared in Example 1 and Comparative Example 1 were respectively subjected to performance tests to measure their strength, hardness and other related material properties. The static performance measurement results are recorded and summarized as shown in Table 1 below.

[0061] Table 1 Material properties test results of different WC alloy samples

[0062]

[0063]

[0064] It can be seen from Table 1 that, compared with Comparative Example 1, the bending strength and of Example 1 are better, and the alloy density and grain size are maintained at a comparable level.

[0065] In addition, the fatigue resistance of the alloy was measured. The test sample size was 20 (± 0.1) mm × 5 (± 0.1) mm × 6 (± 0.1) mm. A universal testing machine was used for fatigue impact test. The stress ratio R = 0.1, the maximum load was 70% of the bending strength, and the frequency was 20 Hz. The fatigue comparison results are shown in Table 2.

[0066] Table 2 Fatigue comparison of different WC alloy samples

[0067]

[0068] The results in Table 2 show that the alloy after the introduction of Mo has better bending strength, and the comprehensive strengthening of the bonding phase and the spheroidization of the WC grain morphology bring better fatigue impact resistance to the cemented carbide.

[0069] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A toughened cemented carbide with improved WC grain morphology, characterized in that: It is composed of the following raw materials in percentage by weight: Molybdenum carbide 0.5-5%, cobalt 10-15%, chromium carbide 0.5-3%, and the balance is WC.

2. A toughened cemented carbide with improved WC grain morphology according to claim 1, characterized in that: The molybdenum carbide is Mo2C and / or MoC.

3. A method for preparing a toughened cemented carbide with improved WC grain morphology, characterized in that: The following steps are involved: (1) Weighing the raw materials according to the mass percentages described in claim 1 or 2; (2) mixing the weighed raw materials and wet-grinding them to obtain a uniform and fine mixture, drying the mixture, sieving the obtained powder, and then pressing it into a compact; (3) The obtained compact is placed in a vacuum low-pressure sintering furnace for dewaxing and sintering to obtain a toughened cemented carbide with improved WC grain morphology.

4. The method for preparing a toughened cemented carbide with improved WC grain morphology according to claim 3, characterized in that: The wet grinding medium in step (2) is hexane, the ball milling speed is 60-80 r / min, the grinding body is a Φ6.35 mm alloy rod, the ball-to-material ratio is 3:1-5:1, and the ball milling time is 18-32 h.

5. The method for preparing a toughened cemented carbide with improved WC grain morphology according to claim 2, characterized in that: The drying in step (2) is vacuum drying, the drying temperature is 70-80° C., and the drying time is 15-30 min.

6. The method for preparing a toughened cemented carbide with improved WC grain morphology according to claim 3, characterized in that: The sieved particle size in step (2) is 40-60 mesh.

7. The method for preparing a toughened cemented carbide with improved WC grain morphology according to claim 3, characterized in that: The pressing method in step (2) is to press into a green compact at a pressure of 8-10 MPa and maintain the pressure for 5-10 seconds.

8. The method for preparing a toughened cemented carbide with improved WC grain morphology according to claim 3, characterized in that: The dewaxing sintering method in step (3) is: keeping the temperature at 380-420°C for 0.5h, then heating to 1400-1470°C in a vacuum environment, filling with argon to 1MPa-5MPa and sintering for 1-4h.

Citation Information

Patent Citations

  • Method for improving strength and toughness of hard alloy by adding metal oxides

    CN109957697A

  • Rare-earth-added ultra-fine grain high-toughness WC-10Co hard alloy material and preparation method

    CN111088450A